Acute methyl jasmonate exposure results in major bursts of stress volatiles, but in surprisingly low impact on specialized volatile emissions in the fragrant grass Cymbopogon flexuosus - Jiang, Yifan (Journal of plant physiology, 2022)
Copyright © 2022 Elsevier GmbH. All rights reserved.